Eksistensi Strategi Digital Marketing Berbasis Maṣlaḥah dalam Bisnis Islam : The Existence of Maṣlaḥah-Based Digital Marketing Strategy in Islamic Business - Yuli Irawan Rasit; Saiful Mukhlis; Abd Wahab (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
This research aims to analyze and interpret the internalization of maṣlaḥah values in business strategies implemented in Islamic business so that they can bring blessings. This research is field research using a qualitative method and a spirituality paradigm approach in developing business organizations using the basis of maṣlaḥah, which is the goal of doing business in Islam. The results of this research are that the muamalah principle emphasizes the importance of seeking benefit and avoiding harm in all business activities, so that a maṣlaḥah-based digital marketing strategy includes the application of Islamic sharia values, namely the value of ukhuwah Islamiyah, the value of honesty, and the value of kindness. Thus, maṣlaḥah-based digital marketing activities can be a means of building mutually beneficial relationships between consumers and entrepreneurs. Apart from that, this strategy can also be a means of spreading goodness in society.